Significance Of Reproduction Especially Mating And Larval Releasing Of Littoraria scabra (Gastropoda: Littorinidae), In Tombariri Mangrove, North Sulawesi, Indonesia - Lalita, Jans Djoike (Jurnal Moluska Indonesia, 2024)
This study used Littoraria scabra as a model of research that attempted to understand how the species optimize their survival in mangrove area. It was aimed at investigating the reproductive significance of oviviparous L. scabra and larval release periodicity in order to maintain their survival in mangrove ecosystem. Reproductive observations of L. scabra were done by looking at mating, larvae releasing rate. Results showed that the reproductive significance of L. scabra was observed as follows: a) there were 64.58% of mating pairs on the stem of S. ovata; b) Mating L. scabra releasing the larvae did not have gonad reduction; c) L. scabra released significantly larger female larvae than male.Specific significance of ovoviviparous species L. scabra with reproductive patterns, i.e mating, larvae releasing rate, was to optimize their reproductive significance in extreme three-dimensional mangrove habitat. This study concluded that the reproductive significance of male L. scabra possessed a uniqueness and very rare in nature larva storing system and quickly released larvae. This study support research 2016, also found the reproductive significance in which males and females, while mating, released larvae with bi-lunar and tidal cycles.